Boosting the performance of organic cathodes through structure tuning - Xie, Jian (2020)
The decisive factor to realize high-capacity rechargeable batteries is the cathode. Since the experimental capacity of inorganic cathodes is usually less than 200 mA h g−1, searching for new cathode materials to boost the capacity is highly desirable. Here, we design and synthesize two novel organic cathodes, poly(pyrene-4,5,9,10-tetraone) (PPTO) and poly(2,7-ethynylpyrene-4,5,9,10-tetraone) (PEPTO), based on the highly redox-active pyrene-4,5,9,10-tetraone. Due to their four Li+ ion intake characteristics, both cathodes show a large reversible capacity of 234 & 244 mA h g−1 and a high energy density of up to 530 & 507 W h kg−1, respectively. In particular, benefiting from the enhanced conjugation and planarity, PEPTO with the addition of a carbon–carbon triple bond (C[triple bond, length as m-dash]C) delivers a significantly improved rate stability at high current densities and an excellent capacity retention of 110 mA h g−1 after 1000 cycles (at 800 mA g−1). Our approach could provide an effective strategy to prepare new organic cathodes for the next generation of high stability and high energy density organic batteries through structure tuning.